2020
DOI: 10.1038/s41598-020-72168-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased blood BACE1 activity as a potential common pathogenic factor of vascular dementia and late onset Alzheimer's disease

Abstract: Late onset Alzheimer disease (LOAD) is traditionally considered as a separate disease from vascular dementia (VAD). However, growing evidence suggests that β-amyloid (Aβ) accumulation, that initiates LOAD-related neurodegeneration, is preceded by vascular events. Previous in vitro studies showed that β-secretase 1 (BACE1), the key-enzyme of amyloidogenesis, is upregulated by cerebrovascular insult; moreover, its activity is increased both in brain and serum of LOAD patients. We aimed to investigate whether BAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
(74 reference statements)
3
19
0
Order By: Relevance
“…By investigating a much larger sample of older individuals, we confirmed the finding of higher levels of serum BACE1 activity LOAD compared to controls, showing that this difference is independent of possible confounders including age, gender, and other risk factors for dementia (Cervellati et al, 2020). More recently, we found that BACE1 serum activity is significantly higher also in VD and MIXED (LOAD + VD), but not in other types of dementia, compared with controls (Zuliani, Trentini, et al, 2020).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…By investigating a much larger sample of older individuals, we confirmed the finding of higher levels of serum BACE1 activity LOAD compared to controls, showing that this difference is independent of possible confounders including age, gender, and other risk factors for dementia (Cervellati et al, 2020). More recently, we found that BACE1 serum activity is significantly higher also in VD and MIXED (LOAD + VD), but not in other types of dementia, compared with controls (Zuliani, Trentini, et al, 2020).…”
Section: Introductionmentioning
confidence: 84%
“…Analyses were performed by SPSS for Windows statistical package, version 13.0. No sample calculation was performed and the number of subjects was determined on previous studies (Cervellati et al, 2020; Shen et al, 2018; Zuliani, Trentini, et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, inspired by mounting evidence of BACE1 increase in brain, CSF, and plasma, in AD patients compared to healthy controls [ 1 ], we have started to evaluate the diagnostic performance of serum activity of the enzyme. Taking a stock of our results, from the analysis of total 817 subjects, we have found that serum BACE1 activity is around 30% higher in patients with AD, vascular dementia (VD), mixed dementia (AD & VD) compared to controls [ 3 , 4 ]. Then, we moved the lens to amnestic and non-amnestic mild cognitive impairment (a- and na-MCI, respectively), with the former being more prone to convert into AD compared to the latter [ 5 ].…”
mentioning
confidence: 99%
“…BACE1 concentration and activity have been found to be elevated brain and cerebrospinal fluid (CSF) of AD patients compared with normal individuals. Intriguingly, two recent large population studies [ 2 , 3 ] from our group demonstrated that this alteration is also reflected in periphery, with a 30% increase in serum BACE1 activity in AD patients compared to controls. This finding is supported by some elegant investigations from Hampel’s group [ 4 , 5 ], showing both a correlation of peripheral BACE1 with well-established AD markers (CSF Aβ and t-Tau), and with axonal degeneration and brain atrophy in individuals at high risk for AD.…”
mentioning
confidence: 55%